2004
DOI: 10.1002/mds.10713
|View full text |Cite
|
Sign up to set email alerts
|

A 100% increase of dopaminergic cells in the olfactory bulb may explain hyposmia in Parkinson's disease

Abstract: Hyposmia is one of the most prevalent symptoms of Parkinson's disease. It may occur even before the motor symptoms start. To determine whether the olfactory dysfunctions, like the motor symptoms, are associated with a loss of dopamine, the number of dopaminergic cells in the olfactory bulb of Parkinson's disease patients was studied using tyrosine hydroxylase immunohistochemistry. The quantitative analysis reveals that the total number of tyrosine hydroxylase-immunoreactive neurons in the olfactory bulb is twi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
194
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(218 citation statements)
references
References 38 publications
13
194
1
4
Order By: Relevance
“…This further indicates that tg ␣-syn directly induced progressive motor decline and, additionally, that disease progression depends on continuous presence of transgene expression. However, the nonreversibility of symptoms in treated CaM_␣-syn mice suggested that neurodegeneration and nigral axon pathology was not ameliorated by a compensatory effect as increased neurogenesis, which might be a frequent response to injury in rodents (Arvidsson et al, 2002;Nakatomi et al, 2002;Zhao et al, 2003;Winner et al, 2006) and human brain (Huisman et al, 2004). Analysis of neurogenesis of 6-month-old CaM_␣-syn mice consistently revealed a negative impact on progenitor cells in the granular cell layer of the dentate gyrus.…”
Section: Discussionmentioning
confidence: 99%
“…This further indicates that tg ␣-syn directly induced progressive motor decline and, additionally, that disease progression depends on continuous presence of transgene expression. However, the nonreversibility of symptoms in treated CaM_␣-syn mice suggested that neurodegeneration and nigral axon pathology was not ameliorated by a compensatory effect as increased neurogenesis, which might be a frequent response to injury in rodents (Arvidsson et al, 2002;Nakatomi et al, 2002;Zhao et al, 2003;Winner et al, 2006) and human brain (Huisman et al, 2004). Analysis of neurogenesis of 6-month-old CaM_␣-syn mice consistently revealed a negative impact on progenitor cells in the granular cell layer of the dentate gyrus.…”
Section: Discussionmentioning
confidence: 99%
“…The pathological substrate for this olfactory loss is not clear, some studies reporting conflicting information about damage to the olfactory epithelium or changes in olfactory bulb volumes as potential sources of these deficits (Muller et al, 2005;Witt et al, 2009;Wang et al, 2011). However, various studies have now reported an increase in the total number of periglomerular dopaminergic cells in the olfactory bulb of parkinsonian patients (Huisman et al, 2004;Morley and Duda, 2010).…”
Section: Early Anosmiamentioning
confidence: 99%
“…Comparable observations have been made in patients with PD, with a decrease in mitotic cells in both the SVZ and hippocampus (the dentate gyrus subgranular zone being the second major area for adult neurogenesis) [91]. Moreover, an increase in dopaminergic olfactory neurons has been described in PD patients, despite their early and progressive loss in the sense of smell [92].…”
Section: Lrrk2 and Neurogenesismentioning
confidence: 96%